Efektivitas Kelembagaan Pemerintah Dalam Pengembangan KEK Tanjung Lesung Kabupaten Pandeglang Provinsi Banten - Meliana, Katrina Doris; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Special Economic Zone (SEZ) Tanjung Lesung located in Pandeglang, Banten Province, was established to increases local economy by tourism. Under law No. 39 year 2009 on SEZ, SEZ was managed by Zone’s board with assistance of SEZ secretariat, its administrator, and company such as PT. Banten West Java (BWJ). Effective institutional productivity is needed in the development of SEZ Tanjung Lesung. This research uses quantitative and qualitative methods to measure effectivity level of its employee’s character, government policy, human resources effectivity, also role and coordination of zone’s board . There is inefficiency in SEZ management mainly in role and coordinating aspects that turns SEZ working inefficently because of the lack of coordination, communication, service standards, monitoring and supervision. Further institutional evaluation and restructurization is needed to ensure optimum SEZ function.